2018
DOI: 10.1002/tafs.10016
|View full text |Cite
|
Sign up to set email alerts
|

Lake Sturgeon, Lake Whitefish, and Walleye Egg Deposition Patterns with Response to Fish Spawning Substrate Restoration in the St. Clair–Detroit River System

Abstract: Egg deposition and use of restored spawning substrates by lithophilic fishes (e.g., Lake Sturgeon Acipenser fulvescens, Lake Whitefish Coregonus clupeaformis, and Walleye Sander vitreus) were assessed throughout the St. Clair–Detroit River system from 2005 to 2016. Bayesian models were used to quantify egg abundance and presence/absence relative to site‐specific variables (e.g., depth, velocity, and artificial spawning reef presence) and temperature to evaluate fish use of restored artificial spawning reefs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…, Fischer et al. ). In contrast, our study suggested these segments were also used for feeding and overwintering.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Fischer et al. ). In contrast, our study suggested these segments were also used for feeding and overwintering.…”
Section: Discussionmentioning
confidence: 98%
“…, Fischer et al. ), but presumably the long‐term residence of lake sturgeon in these segments required access to non‐spawning resources, for example, feeding areas. In general, the segments of high lake sturgeon use in both rivers had diverse invertebrate communities, variable flow rates, complex physical structures, and substrates with mixtures of sand and clay relative to the other segments (see Tables and for comparisons of physical and biological characteristics).…”
Section: Discussionmentioning
confidence: 99%
“…; Krieger and Diana ; Fischer et al. ). In contrast, the Ouareau River site was deemed to have experienced a loss of habitat quantity and function due to a landslide event in 1990 that covered the traditional spawning site (Figure ) with clay and silt deposits.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these impacts, lake sturgeon has since been listed as a threatened species under the State of Michigan's Endangered Species Act (MCL 324.3605, 1994 PA 451) and ranked as a priority for conservation and management in the Great Lake regions (Holey, Baker, Thuemler, & Elliott, ). Rehabilitation efforts including restoration of migratory routes, protection of spawning and non‐spawning habitats and stocking programmes are ongoing as a means to restore lake sturgeon populations throughout the region (Fischer et al, ; Hayes & Caroffino, ; Manny & Kennedy, ; Peterson, Vecsei, & Jennings, ). Hatchery supplementation is widely advocated as an important means to achieve management goals of sustainable populations of this fish (Crossman et al, ).…”
Section: Introductionmentioning
confidence: 99%